Paleoclimate Records of the Middle Okinawa Trough Since the Middle Holocene: Modulation of the Low-Latitude Climate - Liu, Lei; Guan, Hongxiang; Xu, Lanfang; Sun, Zhilei; Wu, Nengyou (Frontiers in Earth Science, 2022)
The ubiquity of glycerol dibiphytanyl glycerol tetraethers (GDGTs) and their temperature sensitivity make them one of the most effective tools for paleoclimate reconstruction. High- and low-latitude climates influence the Okinawa Trough (OT). It receives diverse inputs from the East China Sea, the western Pacific, and the Kuroshio Current, providing good conditions for paleoclimate studies. Here, isoprenoid GDGTs (isoGDGTs), branched GDGTs, and hydroxylated GDGTs (OH-GDGTs) were studied to reconstruct the sea surface temperature (SST) of the central OT for the past 8.2 kyr using the tetraether index of 86 carbon atoms at low latitudes (TEXH86) and the ring index of OH-GDGTs (RI-OH). The GDGT-0/crenarchaeol ratios ranged from 0.39 to 0.98. The branched and isoprenoid tetraether index and the methane index values were lower than 0.1 and 0.5, respectively, indicating that the isoGDGTs were mainly derived from marine Thaumarchaeota and that TEXH86 could be used to reconstruct the paleotemperatures. The TEXH86 SSTs ranged from 21.6–27.2C during 8.2 kyr. The overall range of TEXH86 SSTs is close to the UK’37 SST of the middle OT and reflects the mean annual SST. In contrast, RI-OH temperatures varied from 17.4 to 26.0C, showing a lower trend than TEXH86 SSTs. The core top RI-OH temperature is 24.1C, in line with the mean annual seawater temperature at 40 meters (24.2C) in the study area, which likely reflects the subsurface temperature in this case. The small overall warming trend of TEXH86 SSTs agrees with the increasing intensity of the Kuroshio Current during the last 8.2 kyr, indicating that the SST evolution is governed by the Kuroshio Current that transports heat from the western tropical Pacific. The decreasing temperature differences between TEXH86 and RI-OH and between UK’37 and RI-OH showed increased mixing of the upper water column, which was in good accordance with the increasing low-latitude winter insolation decoupling from the East Asian summer monsoon. The cold event that occurred at 7.4–6.6 kyr was magnified (~5C) at the TEXH86 and RI-OH temperatures and possibly caused by tephra's significant input (~7.3 kyr).